Evaluation of Antioxidant Capacity and Antimicrobial Properties of Ethnic Bambuseae species and Identification of the Active Components - Devi, Arundhuti (International Journal of Pharmaceutical & Biological Archive, 2016)
Evaluation of Antioxidant Capacity and Antimicrobial Properties of Ethnic Bambuseae species and Identification of the Active Components